Importance Performance Map Analysis on Hospital Branding toward Hospital Choice Intention - Wiyono, Stevie Pramudita; Antonio, Ferdi (Universitas Muhammadiyah Yogyakarta, 2024)
The development of hospitals in Indonesia is increasing every year. Due to inevitable competition between hospitals, hospital management has to try to improve hospital branding, which can be an opportunity for hospitals to attract new patients and retain patients. In this study, brand benevolence, brand reliability, brand prestige, and brand sincerity were used in the Importance Performance Map Analysis (IPMA) analysis of hospital choice intention. IPMA analysis uses SmartPLS 4.0.9.6 software with online and offline survey data collection methods for all patients who have visited an Indonesia type C private hospital (>100 beds) in the last year. Data collection was carried out in April 2024, obtaining 292 respondents who met the predetermined inclusion criteria. The results show that brand benevolence and brand reliability are included in high importance and high performance, while brand prestige is included in high importance and low performance, which must be considered by hospital management. Meanwhile, brand sincerity is included in the low-importance and low-performance categories. Hospital management must pay attention to brand prestige, which can increase patient satisfaction and hospital revenue in the long term. The study contributes to the understanding of hospital choice intention by highlighting the importance of hospital branding in shaping patient decisions.